2019
DOI: 10.4274/jcrpe.0162
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Premature Small For Gestational Age Infants Have Appropriate Catch-Up Growth At Term Equivalence Compared With Extreme Premature Appropriate For Gestational Age Infants

Abstract: Our study shows that extreme premature SGA infants have appropriate catch up growth by the time they reach term equivalence suggesting that postnatal nutrition and care are important determinants of catch-up growth in SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Postnatal growth is divided into the infancy, childhood, and adolescent periods, and growth failure in any of these periods increases the possibility of short stature in adulthood [ 22 , 23 ]. Growth in early childhood, particularly during the 24 months after birth, has an impact on growth in later childhood and puberty [ 24 ], ultimately leading to final adult height.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal growth is divided into the infancy, childhood, and adolescent periods, and growth failure in any of these periods increases the possibility of short stature in adulthood [ 22 , 23 ]. Growth in early childhood, particularly during the 24 months after birth, has an impact on growth in later childhood and puberty [ 24 ], ultimately leading to final adult height.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to have a lower risk for insulin resistance and cardiovascular disease, as long as they receive a restricted food supply in later life as in their prenatal period (1,2,3,4). Ng et al (5) reported that extremely premature SGA infants achieved catch up growth with postnatal nutrition, but they tend to have a greater risk of insulin resistance, type 2 diabetes, polycystic ovarian syndrome, hypertension, hyperlipidemia and coronary artery disease because of nutritional thrift.…”
Section: Dear Editormentioning
confidence: 99%